Quantitative analysis of gel electrophoretograms by image analysis and least squares modeling - Vohradský, J; Pánek, J (Electrophoresis, 1993)
A computer-aided quantitative method for a complex analysis of gel electrophoretograms is presented. The analysis consists of several steps: (i) determination of the background image by methods of mathematical morphology and its subtraction from the gel image, (ii) selection of an appropriate part of the gel lane including curved lanes and lanes with a nonuniform width, (iii) computation of the lane densitogram by averaging several lane-parallel scans, (iv) decomposition of the lane densitogram into component bands using a data selecting algorithm and Marquardt's minimizer. Several different functions for component bands are utilized. It is shown that the densitogram can be decomposed into component bands with reasonable accuracy only if an appropriate model function is chosen. The algorithms are tested on several different gel electrophoretograms which show typical features as a nonuniform background, curved lanes, an asymmetrical band shape and a superposition of small bands on the shoulders of big ones. It is shown that overlapped bands are best approximated by an asymmetrical Gausian curve and an asymmetrical Gauss-Cauchy function. Linear response to the serial dilution of the protein sample is tested.
Keywords: elektroforéza v agarovém gelu; Electrophoresis, Polyacrylamide Gel; Escherichia coli; Mathematics; DNA bakterií; DNA, Bacterial; ribozomální proteiny; Densitometry; Proteins; Least-Squares Analysis; metoda nejmenších čtverců; Electrophoresis, Agar Gel; denzitometrie; proteiny; molekulová hmotnost; počítačové zpracování obrazu; plazmidy; Ribosomal Proteins; matematika; Streptomyces aureofaciens; Plasmids; Molecular Weight; elektroforéza v polyakrylamidovém gelu; Image Processing, Computer-Assisted